Communication Service Strategy in Building Alumni Loyalty of Umrah Congregations at PT Madani Alam Semesta Tour and Travel, Garut Branch - Muhammad Saepul Ulum; Anton Widodo; Andi Rahmad; Agam Anantama (Sosiosaintika, 2026)
The tight competition in the Umrah travel industry requires companies to implement effective service communication strategies rooted in Islamic values to retain customers. This study aims to analyze service communication strategies in building loyalty among Umrah pilgrim alumni; its novelty lies in integrating Islamic brotherhood values throughout the service process. A descriptive qualitative approach was used, with data collected through in-depth interviews, observation, and documentation at PT Madani Alam Semesta Tour and Travel, Garut Branch. The results show that consistent two-way communication is applied before, during, and after worship, using digital platforms, guidance sessions, and post-service programs. This strategy effectively enhances satisfaction and trust, leading to long-term loyalty reflected in repeat participation and positive recommendations.